2017
DOI: 10.1093/nar/gkx801
|View full text |Cite
|
Sign up to set email alerts
|

RNA guanine-7 methyltransferase catalyzes the methylation of cytoplasmically recapped RNAs

Abstract: Cap homeostasis is a cyclical process of decapping and recapping that impacts a portion of the mRNA transcriptome. The metastable uncapped forms of recapping targets redistribute from polysomes to non-translating mRNPs, and recapping is all that is needed for their return to the translating pool. Previous work identified a cytoplasmic capping metabolon consisting of capping enzyme (CE) and a 5′-monophosphate kinase bound to adjacent domains of Nck1. The current study identifies the canonical cap methyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 36 publications
3
91
0
Order By: Relevance
“…, against nucleolin and tubulin) can determine whether cross-contamination occurred during the fractionation procedure. For an example of expected Western blot results, see Figure 1C of Trotman et al , 2017.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…, against nucleolin and tubulin) can determine whether cross-contamination occurred during the fractionation procedure. For an example of expected Western blot results, see Figure 1C of Trotman et al , 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The N7 methyl group is particularly critical for the mRNA life cycle, as it drastically increases the binding affinity of cap-binding proteins (Niedzwiecka et al , 2002) and protects mRNAs from cap-quality control surveillance mechanisms (Jiao et al , 2013). We recently reported that the mammalian RNA guanine-7 methyltransferase (RNMT) functions beyond its canonical role in nuclear co-transcriptional cap synthesis to participate in cytoplasmic RNA recapping (Trotman et al , 2017). We used the protocol presented here to demonstrate that the cap methyltransferase activity of cytoplasmic RNMT is unexpectedly robust relative to nuclear RNMT.…”
Section: [Background]mentioning
confidence: 99%
See 3 more Smart Citations